Memorandum of Understanding between the BDI, BRAC University and Asia Foundation to establish and maintain a Secretariat that will serve as a regional coordination centre for future activities supporting Women MP's from eight South Asian Countries to implement the action plans developed at the Conference (2012) - The Asia Foundation; BDI, BRAC University (The Asia Foundation and BDI, BRAC University, 2013)
Memorandum of Understanding between the BDI, BRAC University and Asia Foundation to establish and maintain a Secretariat (as follow up to the Regional Women MP's Conference) that will serve as a regional coordination centre for future activities supporting Women MP's from eight South Asian Countries to implement the action plans developed at the Conference (2012).